Microstructural Characteristics of 3Y-TZP Ceramics and Their Effects on the Flexural Strength - Alves, Manuel Fellipe Rodrigues Pais; de Campos, Leonardo Queiroz Bueno; Simba, Bruno Galvão [UNESP]; da Silva, Cosme Roberto Moreira; Strecker, Kurt; dos Santos, Claudinei (MDPI, 2022)
This work evaluates the effects of grain growth and tetragonality of the t-ZrO2 phase on the mechanical properties of 3Y-TZP ceramics. Samples were sintered at 1475 °C for 2 h, and at 1600 °C for 2, 12, or 24 h. After sintering, the tetragonal ZrO2 polytypes t and t′ were observed under all sintering conditions, while a residual content of monoclinic ZrO2 was detected in samples sintered at 1600 °C for 24 h. The average grain size was found to vary from 0.65 ± 0.10 to 2.20 ± 0.35 μm. Moreover, zirconia ceramics sintered at 1475 °C for 2 h exhibit higher flexural strength (1210 ± 85 MPa), while samples sintered at 1600 °C for 24 h exhibit the lowest flexural strength (910 ± 90 MPa). These results were related to the progressive formation of Y3+-rich grains (t′-ZrO2) due to the grain boundary segregation-induced phase (GBSIPT) mechanism. Due to the high stabilizer concentration in the solid solution, these grains present lower tetragonality, being highly stable at room temperature. Consequently, the observed strength reduction of samples sintered at 1600 °C for 24 h is related to the presence of the t′-ZrO2 phase, which is less prompt to the phase transformation toughening process, limiting shielding zones’ effectiveness at the crack tip.
Keywords: mechanical properties; microstructure; phase transformation; tetragonality; Y-TZP